Al-Iqna' fi halla alfadh abi shuja - Al-Sharbini al-Khatib
An excellent new edition for one of the best explanations of one of the most famous treatises in Shafi'i Fiqh, Matn Abi Shuja', written by Al-Khatib ach-Sharbini (977H).This new and very serious edition is based on numerous manuscripts, both for the Matn and for al-Iqna'. One of the special features of this edition is that it is linked to the Matn Abi Shuja' published by the same Muhaqqiq, who has marked each Fiqh question in the Matn with a number (5923 points in all). Thus he matches Al-Khatib ash-Shirbini's Al-Iqna' with its same points, thus allowing for continuity in the study of the Matn and its understanding. The Sharh of Al-Bijirmi which we also offer in this same edition also corresponds with this numbering.There are also numerous footnotes that complete the explanation, notably on sources, proper names, and some additional Fawaid.